2002
DOI: 10.1099/00221287-148-11-3737
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene, an insect repellent, is produced by Muscodor vitigenus, a novel endophytic fungus

Abstract: Muscodor vitigenus is a recently described endophytic fungus of Paullinia paullinioides, a liana growing in the understorey of the rainforests of the Peruvian Amazon. This fungus produces naphthalene under certain cultural conditions. Naphthalene produced by M. vitigenus was identified by gas chromatography/mass spectrometry. Its chromatographic and mass spectral properties were identical to authentic naphthalene. Agar plugs supporting growth of the fungus and producing known amounts of naphthalene effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(119 citation statements)
references
References 8 publications
2
114
0
3
Order By: Relevance
“…Although the VOCs appear in differing amounts and ratios, the compound in greatest abundance in all of the new isolates of M. albus is naphthalene (Table 2). This is comparable to M. vitigenus, whose only detectable VOC is naphthalene (Daisy et al, 2002b).…”
Section: Voc Production By the New Isolates Of M Albusmentioning
confidence: 58%
See 2 more Smart Citations
“…Although the VOCs appear in differing amounts and ratios, the compound in greatest abundance in all of the new isolates of M. albus is naphthalene (Table 2). This is comparable to M. vitigenus, whose only detectable VOC is naphthalene (Daisy et al, 2002b).…”
Section: Voc Production By the New Isolates Of M Albusmentioning
confidence: 58%
“…Interestingly, no individual compound by itself possessed major antifungal activity, but a combination of compounds was required, as was previously determined for M. albus isolate CZ-620 . It was also previously noted that naphthalene, the sole distinguishing VOC of M. vitigenus, was produced in great enough quantities to cause modifications in insect behaviour (Daisy et al, 2002b (Stinson et al, 2003a). Initially it was thought that M. albus was a unique organism confined to only one locale, but as more studies are done, it appears that it and related organisms are common inhabitants of the world's tropical rainforests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically in fungi, different cultures of Muscodor albus generated a mixture of volatile organic compounds the most abundant being naphthalene (Ezra et al 2004). Daisy et al (2002) also reported the production of naphthalene under certain cultural conditions by Muscodor vitigenus. Naphthalene generated by this fungus effectively repelled the adult stage of the wheat stem sawfly, Cephus cinctus.…”
Section: Introductionmentioning
confidence: 99%
“…Nodulisporic acids, novel indole diterpines, isolated from Bontia daphnoides that exhibited potent insecticidal properties against the larvae of bowl fly, worked by activating insect glutamate-gated chloride channel (Demain 2000). Daisy et al (2002) isolated another endophytic fungus, Muscodor vitigenus, from liana plant (Paullina paullinioides), which yielded naphthalene as major product. It could be used as active ingredient against common mothballs.…”
Section: Products Of Endophyte With Insecticidal Activitiesmentioning
confidence: 99%